Factors of job burnout among chefs in Malaysia - Abdul Hadi, Arnieyantie; Ungku Zainal Abidin, Ungku Fatimah; Othman, Mohhidin; Md Nor, Norfezah (Human Resource Management Academic Research Society, 2018)
Job burnout in the service industry can bring harmful impact compared to nonservice industries. Chef professions are frequently exposed to negative physical and psychological demand, such as tight time constraint within poor physical working environment. This unfavorable condition can be tiring and may develop towards job burnout. Many factors of job burnout have been widely identified by human resource researchers, however with less focused within the food and beverage industry specifically on Malaysian kitchen workers. The objective of this study is to identify the predictors of job burnout by adopting the job demand resources (JD-R) model. This study adopted desk research and systematic review on previous literature regarding job burnout in service industry. This study found that role conflict, job autonomy, physical work environment and job satisfaction are the factors of job burnout. The output of this study may assist managers on identifying the factors of job burnout that may affect their staff performance. Apart from that, the result may also assist managers to develop strategies to combat job burnout in the workplace.